Pengaruh Motivasi, Kompensasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan PT Indosat Kota Kediri - Daniel Kristianto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This research aims to explain the significant influence of Motivation, Compensation and Job Satisfaction on Employee Performance at PT. Indosat. This research data was obtained from the results of respondents' responses (questionnaires) as well as other research results that are relevant to the object under study. In this case primary data from employees of PT. Indosat with a sample of 55 respondents and used non probability sampling as a sampling technique. The analysis used in this research is multiple linear regression analysis using the SPSS program. The results of this research show that the tcount value is 2.644 > ttable 2.085, so the Motivation variable partially has a significant effect on Employee Performance, then the Compensation variable has a tcount value of 2.808 > ttable 2.085, so the Compensation variable partially has a significant effect on Employee Performance and Job Satisfaction, the tcount value is 2.871 > ttable. 2.085, then the Job Satisfaction variable partially has a significant effect on Employee Performance. Simultaneously the variables Motivation, Compensation and Job Satisfaction influence employee performance at PT. Indosat with Fcount results of 32.421. Apart from that, the results obtained from the Determination Coefficient were 0.809. This indicates that the independent variable has a significant and positive effect on the dependent variable.